Informational district administrative relationships and their effects on the implementation of educational policies - Mina, Primo A. 1929- (s.n.], 1967)
This study described the informal administrative relationship among school officials, government functionaries, and community leaders in some aspects of school administration in a public elementary school district in order to have a better understanding of school administration.